2016
DOI: 10.1039/c6cy00294c
|View full text |Cite
|
Sign up to set email alerts
|

Towards stable single-atom catalysts: strong binding of atomically dispersed transition metals on the surface of nanostructured ceria

Abstract: Surface oxygen sites on CeO2 nanostructures are able to bind atoms of various transition metals strong enough to prevent their sintering. This finding opens a knowledge-driven way to prepare stable single-atom catalysts with maximum metal efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 71 publications
4
72
0
Order By: Relevance
“…It seems important that the catalytic activity in this case sharply drops, and CO oxidation is not observed at temperatures below 100 °C, which is typical of Pt/CeO 2 samples in which platinum is only in the Pt 2+ state. It was noted that Pt 2+ ions interact with the CeO 2 surface to produce strong and stable Pt 2+ –O 4 complexes, which can hardly ensure the low‐temperature oxidation of CO. The oxide PtO x species can interact with ceria and be encapsulated by the upper layers of ceria, as was demonstrated by Mullins and Zhang .…”
Section: Discussionmentioning
confidence: 99%
“…It seems important that the catalytic activity in this case sharply drops, and CO oxidation is not observed at temperatures below 100 °C, which is typical of Pt/CeO 2 samples in which platinum is only in the Pt 2+ state. It was noted that Pt 2+ ions interact with the CeO 2 surface to produce strong and stable Pt 2+ –O 4 complexes, which can hardly ensure the low‐temperature oxidation of CO. The oxide PtO x species can interact with ceria and be encapsulated by the upper layers of ceria, as was demonstrated by Mullins and Zhang .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been reported recently on this topic . For instance, a recent investigation has shown the capability of CeO 2 (1 0 0) to bind highly dispersed single transition metal atoms from groups VIII–X . Jones et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the adsorption of metal atoms (M) including the 3d (Fe, Co, Ni, Cu), 4d (Ru, Rh, Pd, Ag) and 5d (Os, Ir, Pt, Au) metals of groups 8-10 was investigated. 82 The calculated adsorption energies are shown in Fig. 8 Clear trends emerge along the rows and groups of the periodic table (Fig.…”
Section: Parameters Controlling Proton Exchange Membrane Fuel Cell Pementioning
confidence: 99%